The Relationship Of Knowledge And The Level Of Income Of The Parent With The Incidence Of Anemia In Young Women In SMPN 25 Banjarmasin - Rina Alkahfi; Dini Rahmayani; Diky Kurniawan (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Anemia is a problem of nutrition in Indonesia. According to RISKESDAS 2013 Genesis anemia based on age group 5-14 years 15-24 years 26.4%, 18.4%, in South Kalimantan province alone according to figures Dinskes Prov. KALSEL 2015 results from the examination of HB to 15,600 young women showed the results of 49% Suffering from anemia one of them is in school SMPN 25 Banjarmasin as much as 75% of 40 people 30 of them positive anemia.The object of the research: Analyzing the relationship of knowledge and the level of income of the parent with the incidence of Anemia In young women in SMP 25 Banjarmasin.Methods: This research uses the approach of Cross-sectional, a collection of data is done to 60 young women in SMP 25 Banjarmasin by way of systematic random sampling.Results: The results of the analysis of the test statistic with Spearman Rank retrieved value p = 0.276 for the knowledge of parents and p = 0.167 parent income level for young women in SMP 25 Banjarmasin above value α = 0.05 (p 0.05).Conclusion: It was concluded that there is no relationship between the knowledge and the level of income of the parent with the incidence of anemia in young women in SMP 25 Banjarmasin. Keywords: Anemia of young, knowledge of parents, parents ‘ incoming levels